ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA SMP DALAM PEMBELAJARAN TATAP MUKA TERBATAS PADA MATERI HIMPUNAN - Maulidya Rahmah Yunita; Adi Ihsan Imami (IKIP Siliwangi, 2022)
Face-to-face learning is limited to implementation because positive confirmed cases of Covid-19 in Indonesia have decreased. There are various impacts of limited face-to-face learning in the implementation of learning, one of which is mathematics subjects, researchers intend to analyze limited face-to-face learning (PTM) on the ability to understand mathematical concepts of junior high school students in the set material. This research is a type of qualitative research with a descriptive approach. The subjects taken in this study were 20 students of grade VII junior high school in one of the junior high schools in Karawang. The research instrument used is through a test instrument with a total of 4 questions. The results of the analysis obtained no students with very high categories (0%), 2 students with high categories (10%), 11 students with sufficient categories (55%), 6 students with low categories (30%), and 1 student with very low categories (5%). So that based on the results of the analysis, it can be concluded that the ability to understand students' mathematical concepts in limited face-to-face learning (PTM) in one of the junior high schools in Karawang is included in the sufficient category.